Effects of three months treatment with sertraline on intraocular pressure and cup-to-disc ratio in patients with anxiety disorders/mixed anxiety and depressive disorder/major depressive disorder and without underlying eye disease - Narjes Hendouei; Samaneh Farnia; Hamid Bazyari; Hanieh Ahmadi; Nasim Tabrizi; Athena sharifi_razavi (Mazandaran University of Medical Sciences, 2017)
Exposure to selective serotonin reuptake inhibitors causes pupillary dilator muscle stimulation, active mydriasis, rapid rise in the level of the intraocular pressure (IOP), damage to the optic nerve at the back of the eye, and ultimately leads to acute angle closure glaucoma. The aim of this study was to assess the effects of sertraline on the levels of IOP and cup-to-disc ratio (CDR) in patients with anxiety disorders or mixed anxiety and depressive disorder or major depressive under daily treatment with sertraline and without underlying eye disease for three months. In this study,30 eligible patients in the sertraline group and 30 healthy volunteers in the control group include the study and were referred to an ophthalmologist. Ophthalmologic examinations were assessed at the baseline and on the first and third months of the study. The average daily dose of sertraline was 95±2.5 mg.During the study, the IOP changes in the sertraline and control groups were 0.26±0.43 and 0.00±0.00 mmHg (p<0.001, p=NS) respectively and the CDR changes in sertraline and control groups were 0.03±0.05 and -0.01±0.05 (p=0.002, p=0.03) respectively. There was a significant difference in the IOP and CDR increasement between two groups ([F (1.7, 104.2) = 3.7, p = 0.03] and [F (2, 116) = 8.3, p < 0.001] respectively). In the present study, although changes in the IOP and CDR  levels in the sertraline group were significant and was equal the daily change in the persons without glaucoma or patients with normal-tension glaucoma, but the slight and continuous increase in the IOP level associated with changes in pupil size and CDR, especially in patients at risk of glaucoma in the long term, can cause a disruption in hydrodynamic homeostasis. More studies with longer duration and different dosage of sertraline need to confirm our results.